Characterization of Expanded Gamma Delta T Cells from Atypical X-SCID Patient Reveals Preserved Function and IL2RG-Mediated Signaling - Tuovinen Elina A; Pöysti Sakari; Hamdan Firas; Le Kim My; Keskitalo Salla; Turunen Tanja; Minier Léa; Mamia Nanni; Heiskanen Kaarina; Varjosalo Markku; Cerullo Vincenzo; Kere Juha; et al. (SPRINGER/PLENUM PUBLISHERS, 2025)
Abnormally high γδ T cell numbers among individuals with atypical SCID have been reported but detailed immunopheno typing and functional characterization of these expanded γδ T cells are limited. We have previously reported atypical SCID phenotype caused by hypomorphic IL2RG (NM_000206.3) c.172C > T;p.(Pro58Ser) variant. Here, we have further investigated the index patient's abnormally large γδ T cell population in terms of function and phenotype by studying IL2RG cell surface expression, STAT tyrosine phosphorylation and blast formation in response to interleukin stimulation, immunophenotyping, TCRv gamma sequencing, and target cell killing. In contrast to his αβ T cells, the patient's γδ T cells showed normal IL2RG cell surface expression and normal or enhanced IL2RG-mediated signaling. V delta 2 + population was proportionally increased with a preponderance of memory phenotypes and high overall tendency towards perforin expression. The patient's γδ T cells showed enhanced cytotoxicity towards A549 cancer cells. His TCRvγ repertoire was versatile but sequencing of IL2RG revealed a novel c.534C > A; p.(Phe178Leu) somatic missense variant restricted to γδ T cells. Over time this variant became predominant in γδ T cells, though initially present only in part of them. IL2RG-Pro58Ser/Phe178Leu variant showed higher cell surface expression compared to IL2RG-Pro58Ser variant in stable HEK293 cell lines, suggesting that somatic p.(Phe178Leu) variant may at least partially rescue the pathogenic effect of germline p.(Pro58Ser) variant. In conclusion, our report indicates that expansion of γδ T cells associated with atypical SCID needs further studying and cannot exclusively be deemed as a homeostatic response to low numbers of conventional T cells.